Aquisição e ambientes favorecedores das líquidas no desvio fonológico - Bonini, Joviane Bagolin (2012)
The phonological acquisition is a complex task which occurs during children s development. Along this process, there are children who present difficulties which may cause the Phonological Disorder (PD). The purpose of this study was to verify the favorable environments for liquids acquisition by children with PD. The sample consisted of 214 children diagnosed with PD who formed a corpus of 15,566 words, transcribed through the Child s Phonological Assessment. The words were collected and analyzed considering the linguistic variables number of syllables, tonicity, word and syllable position, preceding and following context, and about the extralinguistic variables, the study considered severity of phonological disorder, acquisition level, age group and sex. The data were analyzed through the statistical program GOLDVARB 2001 and VARBWIN for each liquid. After that, the privilege value was calculated for the variables word position, number of syllables, tonicity, preceding and following context. For the lateral liquid /l/, the following variables were selected as significant, as well as their favorable factors: level of acquisition (acquired); severity (mild disorder); tonicity (post-tonic); and preceding context ( [ɔ], and empty). The variables age group, number of syllables and sex were also selected as significant. However, they presented only neutral and not favorable factors. For the lateral liquid //, the following variables were selected with their favorable factors: level of acquisition (acquired); severity (mild disorder); and following context ([ɔ]). The variable sex was also selected as significant by the program, but it presented only neutral and not favorable factors. About the non-laterals, the /r/ presented the following variables selected as significant with their following favorable factors: age group (6:7 to 6:12); level of acquisition (partially acquired and acquired); severity (mild disorder); word position (medial onset); and number of syllables (monosyllable). The variables tonicity and sex were also selected as significant. However, they presented only neutral and not favorable factors. Besides, the nonlateral liquid /R/ had as significant and favorable the following variables and factors: severity (mild disorder); tonicity (post-tonic); level of acquisition (acquired); number of syllables (monosyllables). About results of the research, it was possible to conclude that the atypical acquisition and the environments are different from the typical acquisition. Moreover, it was concluded that the lateral and non-lateral liquids present different environments and fostering values. These facts tend to contribute to therapy, because they facilitate the selection of target sounds for the therapeutic process.